PENGELOLAAN BANK SAMPAH CANGKRINGSARI BERSERI DESA CANGKRINGSARI KECAMATAN SUKODONO KABUPATEN SIDOARJO BERBASIS WEB DAN MOBILE - Atik Widiyanti; Laily Noer Hamidah; Ardhana Rahmayanti; Yanuar Risah Prayogi; Zulifah Chikmawati; Qurrota A’yuni (Universitas Nahdlatul Ulama Sidoarjo, 2019)
Cangkringsari Village is located in Sukodono District, Sidoarjo Regency. This village has a population of 1729 people so it produces ± 517.8 kg / day of waste. Waste management especially RW 3 is carried out by the Cangkringsari Berseri waste bank. Cangkringsari Berseri garbage bank is able to serve 66 households out of 125 households. Until now, administrative management is still done manually so that administration runs slowly. In addition, the lack of understanding of the management technology of waste bank administration causes waste management in Cangkringsari Village RW 3 to be less than optimal. To overcome these problems, the method used in this service program is to conduct socialization and training on web-based and mobile waste bank applications. Based on the results of the questionnaire showed an increase of 74% of citizens' understanding of waste bank management technology.